2021
DOI: 10.3389/fpsyg.2021.636116
|View full text |Cite
|
Sign up to set email alerts
|

Usability and User Experience of Cognitive Intervention Technologies for Elderly People With MCI or Dementia: A Systematic Review

Abstract: IntroductionIncorporating technology in cognitive interventions represents an innovation, making them more accessible, flexible, and cost-effective. This will not be feasible without adequate user-technology fit. Bearing in mind the importance of developing cognitive interventions whose technology is appropriate for elderly people with cognitive impairment, the objective of this systematic review was to find evidence about usability and user experience (UX) measurements and features of stimulation, training, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 58 publications
3
35
0
1
Order By: Relevance
“…Almost half of the studies included were pilot or feasibility trials. This shows that there is still a lack of research addressing the use of ATs for older adults at home or in similar settings [ 57 , 62 , 64 ]. A crossover design, where the control group changes to the intervention after a predefined period, was found to be commonly used when evaluating ATs.…”
Section: Discussionmentioning
confidence: 99%
“…Almost half of the studies included were pilot or feasibility trials. This shows that there is still a lack of research addressing the use of ATs for older adults at home or in similar settings [ 57 , 62 , 64 ]. A crossover design, where the control group changes to the intervention after a predefined period, was found to be commonly used when evaluating ATs.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no study has previously explored the association between cognitive function and usability in cognitively unimpaired individuals. However, previous studies using individuals with mild cognitive impairment and dementia have shown that usability measures were poorer in these individuals (they complete fewer tasks, take longer to complete them or need more help) when compared with older adults without cognitive impairment 19 , 20 .…”
Section: Introductionmentioning
confidence: 88%
“…On the other side, humans are easily distracted, lose their interest quickly, or even give up if they get disappointed, confused, or tired. They have limited cognitive resources [e.g., working memory and attention; (43)], and they are often cognitively or emotionally biased (44).…”
Section: Incorporating User-operated Audiometry Within the Existing Clinical Proceduresmentioning
confidence: 99%
“…Making digital technology more user-friendly and measuring the quality of the interaction is a wide field of study of its own and has a fast-growing body of research output in the last few decades. Indicatively, a search in Scopus with keywords [“usability” AND “technology”] yields 717 review studies alone (searched on 8-March-2021), while there is an increasing interest on usability for health evaluation and intervention tools [for reviews see ( 45 47 )]. In the UAud project, the quality of the human-system interaction is crucially important, as deviations from optimum may affect not only the examination, i.e., the first step, but also the whole procedure.…”
Section: Incorporating User-operated Audiometry Within the Existing Clinical Proceduresmentioning
confidence: 99%